Haematologic responses and survival do not significantly decrease with subsequent lines of therapy in systemic immunoglobulin light chain amyloidosis: results from an analysis of real‐world longitudinal data. (29th June 2021) - Ravichandran, Sriram; Cohen, Oliver C.; Law, Steven; Sachchithanantham, Sajitha; Mahmood, Shameem; Foard, Darren; Fontana, Marianna; Martinez‐Naharro, Ana; Whelan, Carol; Gillmore, Julian D.; Lachmann, Helen J.; Hawkins, Philip N.; et al.
Summary: Systemic immunoglobulin light chain amyloidosis (AL) is an incurable disorder, and the natural history is incompletely understood. In this study, we describe its natural history based on an analysis of real‐world longitudinal data. All patients seen at the National Amyloidosis Centre, UK, between February 2010 and August 2019 and treated with up‐front bortezomib are included. In all, 1 276 patients received the first‐line treatment; 259, 85, and 32 patients received second, third, and fourth treatment lines, respectively. Among patients requiring further treatment after the first line, 77·2% started the second line within two years of the first line; 50·5%, 50·6%, 40·1% and 40·6% of patients had achieved at least very good partial response after the first, second, third and fourth treatment lines. Median overall survival (OS) from first, second, third and fourth lines was 45 months, 56 months, 37 months and not reached, respectively ( P  = 0·109). In summary, although relapses occur in AL amyloidosis, the outcomes and responses do not worsen with each subsequent relapse, making it attractive to design therapeutics with curative intent.